A hermeneutical study of the Midrashic influences of biblical literature on the narrative modes, aesthetics, and ethical concerns in the novels of George Eliot - Law-Viljoen, Bronwyn (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1993)
The thesis will examine the influence of Biblical literature on some of the novels of George Eliot. In doing so it will consider the following aspects of Eliot criticism: current theoretical debate about the use of midrash; modes of discourse and narrative style; prophetic language and vision; the influence of Judaism and Jewish exegetical methods on Adam Bede, "The Lifted Veil", The Mill on the Floss, Felix Holt, and Daniel Deronda. Literary critics have, for a long time, been interested in the influence of the Bible and Biblical hermeneutics on literature and the extent to which Biblical narratives and themes are used typologically and allegorically in fiction has been well researched. In this regard, the concept of midrash is not a new one in literary theory. It refers both to a genre of writing and to an ancient Rabbinic method of exegesis. It has, however, been given new meaning by literary critics and theoriticians such as Frank Kermode, Harold Bloom, and Jacques Derrida. In The Genesis of Secrecy, Kermode gives a new nuance to the word and demonstrates how it may be used to read not only Biblical stories but secular literature as well. It is an innovative, self-reflexive, and intricate hermeneutic processs which has been used by scholars such as Geoffrey Hartman and Sanford Budick, editors of Midrash and Literature, a seminal work in this thesis. Eliot's interest in Judaism and her fascination with religion, religious writing, and religious characters are closely connected to her understanding of the novelist's role as an interpreter of stories. In this regard, the prophetic figure as poet, seer, and interpreter of the past, present, and future of society is of special significance. The thesis will investigate Eliot's reinterpretation of this important Biblical type as well as her retelling of Biblical stories. It will attempt to establish the extent to which Eliot's work may be called midrash, and enter the current debate on how and why literary works have been and can be interpreted. It will address the questions of why Eliot, who abjures normative religious faith, has such a profound interest in the Bible, how the Bible serves her creative purposes, why she is interested in Judaism, and to what extent the latter informs and permeates her novels.
Keywords: Eliot, George, 1819-1880 -- Criticism and interpretation; Eliot, George, 1819-1880 -- Language; Eliot, George, 1819-1880 -- Style; Eliot, George, 1819-1880 -- Daniel Deronda; Eliot, George, 1819-1880 -- Felix Holt Eliot, George, 1819-1880 -- Adam Bede; Eliot, George, 1819-1880 -- Mill on the Floss; Midrash -- History and criticism; Midrash -- Hermeneutics; Prophecy in literature; Judaism in literature; Jews in literature; Symbolism in literature